2002
DOI: 10.1063/1.1446876
|View full text |Cite
|
Sign up to set email alerts
|

Space-charge-limited current in cylindrical diodes with finite-length emitter

Abstract: In the present paper we extend to two dimensions the classical Langmuir-Blodgett law, which determines the maximum current I LB that can be accelerated by a given voltage across two infinitely long coaxial cylinders. Generalization of the I LB law is established by performing two-dimensional 2D particle-in-cell numerical experiments on a variety of cylindrical diode configurations with a finite-length emitter. It is found that the limiting current in two dimensions I 2D follows a monotonically decreasing funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…This finding agrees qualitatively to the 2D PIC simulation results, 14 which has showed that the enhancement of the 2D LB law for convergent flow is larger than divergent flow. In the range of ⌫ =3-10 and 0.2Ͻ W / r 2 Ͻ 5, their PIC simulation results for both divergent and convergent flows were numerically fitted with an empirical formula of 1 + 0.1536/ ͑W / r 2 ͒ + 0.0183/ ͑W / r 2 ͒ 2 to within 2.5% for all simulation data.…”
Section: Cylindrical Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding agrees qualitatively to the 2D PIC simulation results, 14 which has showed that the enhancement of the 2D LB law for convergent flow is larger than divergent flow. In the range of ⌫ =3-10 and 0.2Ͻ W / r 2 Ͻ 5, their PIC simulation results for both divergent and convergent flows were numerically fitted with an empirical formula of 1 + 0.1536/ ͑W / r 2 ͒ + 0.0183/ ͑W / r 2 ͒ 2 to within 2.5% for all simulation data.…”
Section: Cylindrical Modelsupporting
confidence: 91%
“…The solid lines are the calculated results at ⑀ = 0 for the convergent flow ͑top͒ and the divergent flow ͑bottom͒. The dash lines are the numerical fitting of 2D PIC simulation,14 which is 1 + 0.1536/ ͑W / r 2 ͒ + 0.0183/ ͑W / r 2 ͒ 2 . It is obvious that the numerical fitted 2D LB law ͑dashed line͒ is no longer accurate at small ⌫ Ϸ 1, which should recovers to 2D CL law ͑for a planar case͒.…”
mentioning
confidence: 99%
“…Most studies in two-dimensions have centred around cold emission from a finite emission area in an otherwise infinite parallel plate geometry [4][5][6]. Note that the Child-Langmuir current is defined in these studies as the current at which oscillatory behaviour sets in (the critical current, J CR ).…”
Section: Introductionmentioning
confidence: 99%
“…As the current density is a function of the dimensionless ration of beam width to anode-cathode gap, the two-dimensional effect has a strong influence on diode current when the emitting plane thickness is much less than the A-K gap. 10,11 Neglecting the influence of the two-dimensional effect, through a simple analytic analysis we know that the current has the relationship with cathode radius and the ratio of anode radius to cathode radius. So the diode current does not increase according to r 2 when d keeps constant in Fig.…”
Section: V-i Relation Of Coaxial Foilless Diodementioning
confidence: 99%